Electrocardiographic characteristics before and after correction of right-sided congenital heart defects in children and its relation to prognosis - Kamphuis, Vivian P.; Raad, Daphne; Nassif, Martina; Swenne, Cees A.; Blom, Nico A.; ten Harkel, Arend D.J. (Journal of electrocardiology, 2019)
Congenital heart defects are the most common birth defects and occur in 0.8% of all live births. Nowadays, patients with congenital heart defects usually survive with many event-free years despite abnormal cardiac hemodynamics. However, most patients still need life-long follow-up and main factors for morbidity and mortality in these patients are cardiac failure, arrhythmias or pulmonary hypertension (PH) [1], The electrocardiogram (ECG) is a noninvasive, widely-used, inexpensive tool that can be used during long-term follow-up of these patients, particularly in order to help predict occurrence of rhythm disorders and sudden cardiac death. From birth to adulthood, several physiological changes influence the cardiac electrical activity. These encompass postnatal circulatory changes and changes due to growth of the body including the heart. Due to the rapid structural and functional changes throughout childhood, interpretation of ECGs in pediatric patients is more challenging than in adults and normal values are always needed for the interpretation of the pediatric ECG. In contrast to adult cardiology, in pediatric cardiology, many congenital heart defects affect the right side of the heart. In this review, we will focus on the ECG of pediatric patients with the most frequent right-sided congenital heart defects: ostium secundum atrial septal defect (ASDII), tetralogy of Fallot (ToF) and pulmonary stenosis (PS).